2008
DOI: 10.1037/a0013078
|View full text |Cite
|
Sign up to set email alerts
|

Two dissociable updating processes in working memory.

Abstract: The authors show that the updating of working memory (WM) representations is carried out by the cooperative act of 2 dissociable reaction time (RT) components: a global updating process that provides stability by shielding WM contents against interference and a local process that provides flexibility. Participants kept track of 1-3 items (digits or Gibson figures). In each trial, the items either were similar to those in the previous trial or were different in any or all of the items. Experiments 1 and 2 estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
129
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(143 citation statements)
references
References 35 publications
12
129
2
Order By: Relevance
“…When it is necessary to update a number which shares many features with that stored in memory, the process can be performed more quickly, as fewer features of the second number need to be activated, because all shared features are already activated. The idea of a selective process of updating is in line with the results obtained by Kessler and Meiran (2008) (see also, Vockenberg, 2006 with other material), showing that updating cost increased along with the number of new items to be memorized. It is noteworthy that in our case, there was only one item to be updated in each trial.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…When it is necessary to update a number which shares many features with that stored in memory, the process can be performed more quickly, as fewer features of the second number need to be activated, because all shared features are already activated. The idea of a selective process of updating is in line with the results obtained by Kessler and Meiran (2008) (see also, Vockenberg, 2006 with other material), showing that updating cost increased along with the number of new items to be memorized. It is noteworthy that in our case, there was only one item to be updated in each trial.…”
Section: Discussionsupporting
confidence: 69%
“…In addition to global updating, Kessler and Meiran (2008) proposed a local updating mechanism that modifies only some elements in WM. They showed that the time required for updating was related to the number of items that had to be substituted.…”
mentioning
confidence: 99%
“…The obvious and acknowledged importance of WM updating stands in contrast to our limited understanding of the underlying processes (for similar arguments, see Kessler & Meiran, 2008;Oberauer & Kliegl, 2001). Kessler and Meiran (2008) argued that updating must involve distinct subprocesses because WM needs to be stable and flexible at the same time.…”
mentioning
confidence: 99%
“…Kessler and Meiran (2008) argued that updating must involve distinct subprocesses because WM needs to be stable and flexible at the same time. Specifically, when updating information, WM must be protected against interference by outdated information, but it must also allow for the modification of memorial content when appropriate.…”
mentioning
confidence: 99%
“…However, the working memory capacity is limited in terms of the number of items that can be activated simultaneously (see Cowan 2001). This implies a flexible updating of the representations activated as a function of new inputs, whilst maintaining the stability of these representations (see Artuso and Palladino 2011;Kessler and Meiran 2008;Morris and Jones 1990). As a consequence, to keep up the pace of processing the incoming sequence of primes, the cerebral cortex must be able to select in real time which associates to a prior prime and/or to a subsequent prime to activate, and which to deactivate in real time (see Whitney et al 2009).…”
Section: Introductionmentioning
confidence: 99%